2011
DOI: 10.21608/ajs.2011.14680
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sowing Dates of Three Cowpea Cultivars on Their Infestation Rate With Cowpea Pod Borer Etiella Zinckenella

Abstract: Field trials were conducted during 2005 and 2006 seasons at Minofia governorate to evaluate the effect of planting date of three cowpea cultivars on their infestation rate with cowpea pod borer, Etiella zienckenella. For each cowpea cultivar planted at each tested date, the numbers of bores and larvae were counted in green and dry pods as well as in dry seeds and the means were obtained to estimate the degree of insect infestations. Results indicated that, regardless the planting date in both seasons, Kream7 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…The present results agree with those of Ekesi et al (1996) and Helalia et al (2011), they stated that the earliest planting date produced significantly high weight of yield. Singh (1999) indicated that cowpea pod borer, E. zinckenella was an important pest and was the main causes of yield losses.…”
Section: On Yieldsupporting
confidence: 93%
See 2 more Smart Citations
“…The present results agree with those of Ekesi et al (1996) and Helalia et al (2011), they stated that the earliest planting date produced significantly high weight of yield. Singh (1999) indicated that cowpea pod borer, E. zinckenella was an important pest and was the main causes of yield losses.…”
Section: On Yieldsupporting
confidence: 93%
“…He concluded that planting date is an important factor for crop production as well as pod-borer infestation level. Helalia et al (2011) stated that early plantation could be involved in reducing E. zinckenella infestation and subsequently increase the cowpea yield.…”
Section: Effect Of the Different Planting Dates: On Etiella Zinckenelmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results agree with those of Saglan and Yasgan (1999), on cucumber recorded that the highest yield (17.53 t/ha) was obtained from the first sowing date in July and from the 3 days harvesting interval. Ekesi et al (1996) and Helalia et al (2011), on cowpea, they stated that the earliest planting date in July produced significantly high weight of yield. Also, Seham et al (1997) and Mohamed (2011) concluded that the different planting date during year effect on the yield, as soon as in the present study.…”
Section: -Effect Of Planting Dates On Yieldmentioning
confidence: 99%
“…The present results agree with those of Saglan and Yasgan (1999), on cucumber recorded that the highest yield (17.53 t/ha) was obtained from the first sowing date in July and from the 3 days harvesting interval. Ekesi et al (1996) and Helalia et al (2011), on cowpea, they stated that the earliest planting date in July produced significantly high weight of yield. Also, Seham et al (1997) Mohamed (2011 and Shaalan H. S. (2016) concluded that the different planting date during year effect on the yield, as soon as in the present study.…”
Section: Spodoptera Littoralis (Boisd) Larvaementioning
confidence: 99%